Student Mastery In Arabic Weak Verbs - Abdul Azim Mohamad Isa; Lily Hanefarezan Asbulah; Muhammad Arsyad Abdul Majid; Fitri Nurul'ain Nordin; Muhammad Firdhaus Zulkifli (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Weak (Muʿtal) verb is one of the aspects studied in Arabic morphology and used as a measure to assess students' abilities. Some students believe they have already mastered Arabic morphology once they can combine common verbs and pronouns very well. This is because, once the pronouns are combined with weak verbs, many students cannot produce the correct weak verb. Thus, the present study aims to survey the level of students’ mastery in Arabic morphology for weak verbs and identify the types of weak verbs that are students’ primary weaknesses. Based on this, a set of multiple-choice tests were distributed to semester one students from the Bachelor of Arabic Language in Professional Communication (LG242) program at UiTM Shah Alam. A purposive sampling technique was employed to test papers that had been administered while in the examination hall. A total of 40 students participated. Instrument reliability analysis recorded items number at 0.82, which is near 1.0 in the interpretation of Cronbach's Alpha score, while item quality showed good individual separating power (person separation exceeding 2.0). Descriptive analysis showed a moderate level of achievement in the students. The final result revealed that this aspect of weak verbs needs to be more emphasized like other aspects of Arabic morphology in the syllabus. The present study uses a quantitative survey method (cross-sectional). The respondents are 40 students in semester one of Arabic Language Professional Communication (LG242) UiTM, Shah Alam. In order to measure students’ level of mastery of the weak verb, a set of written test instruments was administered and distributed to the study respondents. A total of 20 items were adapted from last semester's questions, consisting of 20 questions in the form of multiple-choice questions. Since this item has not been ascertained in terms of its validity and reliability. The researcher conducted a reality and reliability test on the instrument. The study found that the first semester students of the Bachelor of Arabic in Professional Communication UiTM Shah Alam are weak in mastering the morphology of the Arabic language involving the weak type. This situation may occur due to several factors, such as lack of use of weak verbs in making sentences, and lack of revision of weak verbs for a long time after completing the Sijil Tinggi Agama Menengah (STAM) examination, and not mastering verb patterns very well.